Pemberian Diet Tinggi Energi Tinggi Protein Rendah Garam III dan Tinggi Antioksidan pada Pasien Kanker Payudara Stadium IIA: Sebuah Laporan Kasus - Qurrota A’yun Nur Rahmadani; Renatasaskia Nurkusumahputri; Lailatul Muniroh; Sri Sumarmi (Universitas Airlangga, 2024)
Background: Breast cancer ranks first in cases of cancer deaths in Indonesia. The causes of this disease are not completely understood because there are many factors that increase the risk of cancer. The Standardized Nutrition Care Process (NCP) is carried out by providing a High Energy High Protein (HEHP) Low Salt III diet and high in antioxidants to support the patient's improved condition. Objective: To determine the management of NCP in stage IIA breast cancer patients according to the patient's condition. Method: A case study was conducted in March 2021 on patients at Darmo Hospital, Surabaya. Sampling is determined based on emergency considerations and the complexity of the patient's condition. The data collection method was carried out by observation and analysis for 3 days in the patient's intake, physical and clinical, biochemical and anthropometric domains. A literature study was also carried out to complete patient data. Results: In the results of monitoring and evaluation, anthropometric examination there was a constant decrease in the patient's weight, apart from that there was a decrease in leukocyte levels in biochemical examination, in physical and clinical examination there was a constant increase in blood pressure, a decrease in pulse and respiratory rate, body temperature tended to constant and reduced nausea. The patient's intake fluctuates due to the mismatch between the taste of hospital food and the patient's taste. Conclusion: The patient's recovery condition is considered poor in terms of unstable food consumption due to a mismatch between the patient's appetite and the food provided.